What Is the Role of Dietary Inflammation in Severe Mental Illness? A Review of Observational and Experimental Findings - Firth, Joseph; Veronese, Nicola; Cotter, Jack; Shivappa, Nitin; Hebert, James R.; Ee, Carolyn; Smith, Lee; Stubbs, Brendon; Jackson, Sarah E.; Sarris, Jerome (Frontiers in Psychiatry, 2019)
Severe mental illnesses (SMI), including major depression, bipolar disorder and schizophrenia, are associated with increased inflammation. Given diet’s role in modulating inflammatory processes, excessive ‘fast-food’ intake, and lack of adequate nutrition, may contribute towards the heightened inflammation observed in SMI. This review assesses the evidence from observational and experimental studies to investigate how diet and nutrition may affect physical and mental health outcomes in SMI through inflammation-related pathways. Cross-sectional studies indicate that individuals with SMI, particularly schizophrenia, consume more pro-inflammatory foods and fewer anti-inflammatory nutrients than the general population. Cohort studies indicate that high levels of dietary inflammation are associated with increased risk of developing depression, but there is currently a lack of evidence for schizophrenia or bipolar disorder. Randomised controlled trials show that dietary interventions improve symptoms of depression, but none have tested the extent to which these benefits are due to changes in inflammation. This review summarises evidence on dietary inflammation in SMI, explores the directionality of these links, and discusses the potential use of targeted nutritional interventions for improving psychological well-being and physical health outcomes in SMI. Establishing the extent to which diet explains the heightened inflammatory markers observed in SMI is a priority for future research.